Space Corporation Projects: Trends and Perspectives - Khilukha, Oksana (Mykolaiv, 2025)
Abstract. Introduction. The development of spaceships and space corporations is a growing trend. While businesses used to only announce their ambitious plans in the space sector, in recent years, these programs have been put into practice, and the number of private companies entering the space industry has significantly increased. Purpose. The aim of this article is to examine the trends and future prospects of this development, as well as the role of spaceships and space corporations in the system of national economic relations at the national and global levels. Results. The study's theoretical and methodological foundation is based on general scientific methodology, including dialectical analysis and synthesis, statistical observation, comparison, and inductive and deductive reasoning. Information sources include scientific publications; interviews with national and international space industry experts; academic research in astronautics; current legal regulations; and official data from organizations engaged in space activities. The study provides a brief overview of existing private space projects. The most attractive segments of the space sector for private businesses are identified. The article analyzes the significance of private initiatives in developing national space activities. It determines the conditions and factors contributing to the growth of space entrepreneurship. It outlines opportunities and prospects for building a sustainable business model in the space industry. The study focuses on developing the private sector within national space industries and shipbuilding. The study's insights are intended to support government agencies involved in space sector planning, as well as private companies and entrepreneurs looking to successfully manage space-related projects. Conclusions. The research shows that corporate projects are very important for space development. Private businesses drive innovation, offer practical solutions, and play a key role in the commercial space market. Creating favorable conditions for the growth of private space businesses is essential because it will accelerate progress and enhance the domestic space industry and spaceship manufacturing.
Keywords: project; spaceship and space industry; corporations; commercialization; strategic planning.